A spherical fuzzy TODIM approach for green occupational health and safety equipment supplier selection. Issue 1 (2nd January 2021) - Sharaf, Iman Mohamad; Khalil, Essam Abdel-Hadi Ali
ABSTRACT: Spherical fuzzy sets (SFSs) were recently introduced to reflect experts' judgements explicitly and in a more informative manner. TOmada de Decisão Interativa e Multicritério (TODIM) is one of the multi-criteria decision-making techniques. It is founded on the prospect theory that considers the decision-makers psychological behaviours under risk. In this article, TODIM is extended using the novel concept of SFSs to exploit its superior features to incorporate a new point of view in fuzzy decision-making under risk, allowing the decision-makers to express their hesitation independently. To establish the TODIM strategy, two evaluation functions are employed to form the partial dominance degree matrices: the importance evaluation function and the performance evaluation function. A practical example in supplier selection is solved, and a case study on selecting green occupational health and safety (OHS) equipment supplier is given. The results are compared with the results of the spherical fuzzy Technique of Order Preference by Similarity to an Ideal Solution (SF-TOPSIS) and the spherical fuzzy VIsekriterijumska optimizacija i KOmpromisno Resenje (SF-VIKOR). The effect of the attenuation factor of losses on the solution is examined. Finally, a different implementation of the SF-TODIM is used and the processing time of the two implementations is compared.